(untitled) - John M. Nadon (Albany, NY, 1999)
This updated book is the right resource for industrial maintenance technicians who wish to increase their knowledge of electrical theory. In addition to ample basic information for review, new material in this 6th edition includes: scientific and engineering notations, the new and popular brushless DC motors, regenerative braking, and eight common solid state devices- Zener Diodes, LEDs, FETs, UJTs, Op-Amps, Opto-Couplers, Hall-Effect Sensors, and IGBTs. Well-illustrated and with an excellent glossary, this book is an easy way to stay "current" in electricity
Keywords: Electrical engineering